2022
DOI: 10.1186/s13643-022-01893-9
|View full text |Cite
|
Sign up to set email alerts
|

Under detection of depression in primary care settings in low and middle-income countries: a systematic review and meta-analysis

Abstract: Background Depression is one of the commonest mental disorders in primary care but is poorly identified. The objective of this review was to determine the level of detection of depression by primary care clinicians and its determinants in studies from low- to middle-income countries (LMICs). Methods A systematic review and meta-analysis was conducted using PubMed, PsycINFO, MEDLINE, EMBASE, LILAC, and AJOL with no restriction of year of publication… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…There is a missed opportunity that mental illnesses such as depression is left undetected for those who did access primary care services as reported by a recent study where only 7% of depression was detected by primary care clinicians in LMIC [ 32 ]. Previous study in Ethiopia also reported that 98% of depression cases were undetected by primary care clinicians [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a missed opportunity that mental illnesses such as depression is left undetected for those who did access primary care services as reported by a recent study where only 7% of depression was detected by primary care clinicians in LMIC [ 32 ]. Previous study in Ethiopia also reported that 98% of depression cases were undetected by primary care clinicians [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported under-recognition of depression in primary care (Hirschfeld et al, 1997;Fekadu et al, 2020). While symptoms are prevalent, primary care patients do not discuss them with their doctors.…”
Section: Introductionmentioning
confidence: 99%
“…However, research to date suggests that implementation strategies for mhGAP-IG and similar initiatives are not yielding the optimal benefit of these primary care-based strategies. In a recent meta-analysis covering 12 LMICs, the pooled depression detection rate in primary care was 7% [6]. In Kenya, only 5% of primary care facilities detected one or more people with mental illnesses 3 months after training [7].…”
Section: Background and Rationalementioning
confidence: 99%